Extracting growth and inflation expectations from financial market data - Lauri Kajanoja (Bank of Finland, 2004)
This study presents a framework for extracting long-run GDP growth and inflation expectations from financial market data on a real-time basis.The framework uses information from both stock and bond markets.It builds on a dividend discount model of stock valuation and on a linearized consumption Euler equation. Furthermore, expected long-run dividend growth for a broad equity index is assumed to be related to expected long-run GDP growth. Short-run and long-run dividend growth expectations are allowed to differ.The former are measured using equity index futures.We extract growth and inflation expectations for the euro area and for the United States.
URN:NBN:fi:bof-20140807293
Keywords: E31; E44; E66; 330; inflation expectations; growth expectations; equity index futures